A study on transition process to MEB by limiting boiling space - Kendai KAWAKAMI; Shosuke SAKAMOTO; Hirofumi TANIGAWA; Takaharu TSURUTA (Journal of Thermal Science and Technology, 2021)
The study of microbubble emission boiling (MEB) is gaining popularity because it violently emits several microbubbles during subcooled pool boiling, for which the heat flux is greater than the critical heat flux (CHF). Although the occurrence of MEB and the heat transfer mechanisms have been analyzed, several aspects of this phenomenon are unknown. In this study, the behavior of coalesced bubbles that form above the primary bubbles on a horizontal heat transfer surface are focused. Experimental observations of boiling behavior, including the transition process from nucleate boiling to MEB, were conducted under the subcooling condition of 40 °C. The transition from nucleate boiling to MEB was found to occur below the CHF when the boiling space was limited to a height lower than that of the coalescent bubbles. Furthermore, the following two types of transitions were observed, depending on the heat flux considering the restriction of the boiling space: from nucleate boiling to MEB, or from nucleate boiling to film boiling. The restriction of boiling space reduces the condensation rate of coalesced bubbles and increases partial dryout. The surface dryout has two possibilities: promoting the transition to film boiling and reducing the vapor supply to the coalesced bubbles. The latter results in a shrinkage of the coalesced bubbles which induces the direct contact of subcooled liquid to the heat transfer surface. The high heat transfer rate in MEB may be attributed to the direct contact between the solid and liquid, along with microlayer evaporation.